Girls got game : sports stories and poems - Macy, Sue. (New York : Henry Holt & Co., 2001)
A collection of short stories and poems written by and about young women in sports.
1 12 13 16 23 29
Keywords: Sports -- Literary collections; Women athletes -- Literary collections; Sports -- Literary collections; Women athletes -- Literary collections